Outcomes of primary sternal closure for postoperative mediastinitis in children. (12th February 2021) - Tsuji, Shigeto; Ikai, Akio; Oyama, Kotaro; Kin, Hajime; Koizumi, Junichi
Abstract:  : OBJECTIVES: We retrospectively analysed outcomes of debridement and primary sternal closure for postoperative mediastinitis in children. METHODS: Between January 2007 and July 2019, 1285 patients under the age of 20 years underwent congenital heart surgery at the Iwate Medical University. Of these, 22 children had postoperative mediastinitis (1.7%). We performed adequate debridement and primary sternal closure with pectoralis major muscle advancement flaps. We evaluated hospital survival rates, reintervention, duration of intravenous antibiotic treatment, intensive care unit (ICU) stay and hospital stay. RESULTS: The median age and weight at surgery were 12.5 months (range 0–228 months) and 7.8 kg (range 2.2–64.2 kg), respectively. Two patients (9%) had a history of delayed sternal closure. Staphylococcus was the most common causative agent for infection (82%). All cases were categorized as Robicsek's classification type II mediastinitis. The hospital survival rate was 95%, and freedom from reintervention for infectious complications was observed in 91% of the patients. The median durations of intravenous antibiotic treatment, ICU stay and hospital stay were 18 days (range 9–46 days), 4 days (range 1–87 days) and 22.5 days (range 11–87 days). The median follow-up time was 89 months (range 2–148 months), and there was no evidence of recurrent mediastinitis, musculoskeletal growth, physical deformity, breast development and upper trunk or limb movement. CONCLUSIONS: Primary sternal closure is an effective procedure for children as it can significantly shorten treatment duration and reduce physical and psychological burdens. Its results compare favourably with those of conventional therapy in terms of mortality and complications.